2020
DOI: 10.1111/jbi.13774
|View full text |Cite
|
Sign up to set email alerts
|

Local environmental selection and lineage admixture act as significant mechanisms in the adaptation of the widespread East Asian pond skaterGerris latiabdoministo heterogeneous landscapes

Abstract: Aim: Local environmental selection and lineage admixture have long been accepted as important adaptive mechanisms in adjusting widespread taxa to new environments.We studied a pond skater, Gerris latiabdominis, to explore the relative roles played by these two mechanisms in its process of adaptation to heterogeneous landscapes. Location: East Asia.Taxon: Gerris latiabdominis Miyamoto, 1958.Methods: Mitochondrial (COI, COII) and nuclear (ddRAD-seq) markers were sequenced from 202 individuals. Phylogenetic and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Previous phylogenetic studies based on different genes have shown that many members of Chrysanthemum and Ajania are chimeric [ 11 – 14 ]. From the perspective of molecular phylogeny, it has been difficult to identify the main factors leading to the divergence of key traits, such as ray florets and tubular florets, especially environmental, geological, historical, and geographical factors [ 15 ], the effects of which have not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
“…Previous phylogenetic studies based on different genes have shown that many members of Chrysanthemum and Ajania are chimeric [ 11 – 14 ]. From the perspective of molecular phylogeny, it has been difficult to identify the main factors leading to the divergence of key traits, such as ray florets and tubular florets, especially environmental, geological, historical, and geographical factors [ 15 ], the effects of which have not been clearly explained.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, it was concluded that Quaternary climate fluctuation affected the distribution pattern and genetic diversity of C. chinensis. The theory says that the separation and expansion of populations with climate fluctuations lead to gene exchange via lineage admixture [4,95,96]. During ice ages, C. chinensis may retreat to shelters in eastern and southern China.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we suggest that the conclusions drawn exclusively from mitochondrial data might bias inferences of genetic patterns and demographic histories for local endemics. However, as an important independent molecular marker, mitochondria are still recommended in combination with nuclear markers to study the demographic history of a species and are especially suitable for the discovery of speciation mechanisms, such as introgression and incomplete lineage sorting due to mitonuclear discordance (Thanou et al., 2020; Ye et al., 2020; Zhang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%